Analysis of the Status and Tendency of R&D Input in the Field of Rare Diseases Funded by the National Natural Science Foundation of China - Chang, Hanyu; Chu, Wei; Li, Xiaodan; Ma, Jing; Li, Dingguo; Yuan, Ni (Frontiers in Public Health, 2021)
Background: Through collection and sorting of rare disease projects funded by the National Natural Science Foundation, an understanding was gained of the categories of projects funded by the foundation in the field of rare diseases, types diseases, categories of disease systems, regional distribution, distribution of supporting institutions, as well as their dynamic changes, followed by an analysis of focuses and influences of relevant state policies. Method: Through the website of inquiry of projects funded by the National Natural Foundation of China, a retrieval was made concerning the projects funded by the Foundation in the field of rare diseases during the period from 1986 to 2019, followed by descriptive analysis of fund input of rare disease projects, number of projects, temporal and regional distribution, etc. and the analysis of the law of their dynamic changes. Result: As of the end of 2019, there were 57 rare diseases and 678 related projects funded by NSFC, with an accumulated total funding of 253,525,000 yuan. Among the categories of projects, the mostly funded projects were general projects (150,145,000 yuan, 59.22%); among the categories of disease systems, the mostly funded disease system was nervous system (93,186,000 yuan, 37.76%); the mostly funded diseases were multiple sclerosis (34,870,000 yuan, 13.75%); the mostly funded regions were east China (106,987,000 yuan, 42.20%) while the least funded region was northwest China (7,295,000 yuan, 2.88%); among the supporting institutions, the mostly funded institutions were Peking University (24,720,000 yuan, 9.75%) . Conclusion: With promulgation of more policies on encouragement of innovation and accelerated approval procedures, etc., the National Natural Science Foundation of China has been increasing its funding to rare diseases, covering increasingly more categories of funded projects, more types of diseases and wider regions but still relatively weak. Therefore, it’s proposed that the healthy and sustainable development in the course of rare diseases should be promoted through improvement of relevant rare disease policies, encouragement of R&D of medicine for rare diseases, establishment of special funds for rare diseases, acceleration of fund circulation and combination of balanced development and preferential funding to key regions and major diseases.